Bioinspired Polymeric High‐Aspect‐Ratio Particles with Asymmetric Janus Functionalities. Issue 5 (1st March 2021) - Finbloom, Joel A.; Cao, Yiqi; Desai, Tejal A.
Abstract : Polymeric particles with intricate morphologies and properties have been developed based on bioinspired designs for applications in regenerative medicine, tissue engineering, and drug delivery. However, the fabrication of particles with asymmetric functionalities remains a challenge. Janus polymeric particles are an emerging class of materials with asymmetric functionalities; however, they are predominantly spherical in morphology, made from nonbiocompatible materials, and made using specialized fabrication techniques. Herein nonspherical Janus particles inspired by high‐aspect‐ratio filamentous bacteriophage are fabricated using polycaprolactone polymers and standard methods. Janus high‐aspect‐ratio particles (J‐HARPs) are fabricated with a nanotemplating technique to create branching morphologies selectively at one edge of the particle. J‐HARPs are fabricated with maleimide handles and modified with biomolecules such as proteins and biotin. Regioselective modification is observed at the tips of J‐HARPs, likely due to the increased surface area of the branching regions. Biotinylated J‐HARPs demonstrate cancer cell biotin receptor targeting, as well as directional crosslinking with spherical particles via biotin–streptavidin interactions. Finally, maleimide J‐HARPs are functionalized during templating to contain amines exclusively at the branching regions and are dual‐labeled orthogonally, demonstrating spatially separated bioconjugation. Thus, J‐HARPs represent a new class of bioinspired Janus materials with excellent regional control over biofunctionalization. Abstract : Inspired by filamentous bacteriophage, polymeric high‐aspect‐ratio particles with asymmetric Janus functionalities (J‐HARPs) are fabricated with branched morphologies at one end. Maleimide‐bearing J‐HARPs are conjugated with biomolecules, demonstrating regional modification at branching sites. Biotinylated J‐HARPs demonstrate cancer cell targeting and directional crosslinking with microspheres. Bifunctional J‐HARPs with orthogonal reactive handles are fabricated for dual bioconjugation with regiospecificity.